CompTIA Security+ SY0-701 certification guide master cybersecurity fundamentals and pass the SY0-701 exam on your first attempt - Neil, Ian (Packt Publishing Ltd., 2024)
Building on the success of its bestselling predecessor, this third edition of the CompTIA Security+ SY0-701 Certification Guide serves as your one-stop resource for the SY0-701 exam preparation. Written by cybersecurity expert Ian Neil, this comprehensive guide helps you unlock the intricacies of cybersecurity and understand the technology behind the SY0-701 certification, ensuring you approach the exam with confidence. Delving deep into cybersecurity, this book introduces essential principles, controls, and best practices. The chapters are carefully structured to align with the exam objectives of the 701 update, bringing to you the most recent and relevant exam study material. By mastering cybersecurity fundamentals, you'll acquire the knowledge and skills to identify and mitigate threats, manage vulnerabilities, and safeguard enterprise infrastructure. You'll be well-equipped to apply the principles of security governance and compliance, conduct risk assessments, and excel in audit and assessment tasks. The book also contains mock tests to help reinforce your learning and assess your exam-readiness. Whether you aim to excel the CompTIA Security+ SY0-701 exam, advance your career in cybersecurity, or enhance your existing knowledge, this book will transform you into a cybersecurity expert.
Keywords: Computer security -- Study guides -- Examinations; Computer networks -- Study guides -- Security measures -- Examinations; Computer technicians -- Study guides -- Certification; Electronic data processing personnel -- Study guides -- Certification; Sécurité informatique; Examens; Guides de l'étudiant; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant